Fluorinated Phosphonates: Synthesis and Biomedical Application - Romanenko, Vadim D; Kukhar, Valery P (Chemical reviews, 2006)
The chemistry of fluorinated alykylphosphonates is a relatively new area of research, developed mostly over the last two decades. The synthesis, fundamental chemical properties, and biomedical uses of the phosphonic acid derivatives that bear at least one fluorine substituent on the organyl moiety are the subject of this review.